Thickness and crystalline properties of sputtered polycrystalline silicon thin film deposited on Teflon substrates / Shaiful Bakhtiar Hashim, Norhidayatul Hikmee Mahzan and Sukreen Hana Herman - Hashim, Shaiful Bakhtiar; Mahzan, Norhidayatul Hikmee; Herman, Sukreen Hana (2017)
A Polycrystalline silicon (poly-Si) thin film was successfully deposited on Teflon substrates at a room temperature using radiofrequency (RF) magnetron sputtering. The effects of sputtering pressure on the thickness and crystallinity properties of the thin films have been studied. Raman scattering spectrometer which manufactured by Horiba Jobin Yvon was used to measure the crystallinity. Based on the Raman spectroscopy results, it shows that the peak is around 512 cm-1 with 7 mTorr on the Teflon substrates. The crystalline’s quality of the films on the Teflon substrates can be increased by increasing sputtering pressure to indicate the improvement of crystalline quality. Thickness for Teflon substrates was measured by using a surface profiler KLA-Tencor P-6. The results show that the thickness decreases by the increment of sputtering pressure. It can be concluded that, the kinetic energy during the sputtering process strongly influences the properties of deposit film such as crystalline quality and film density.